ANALISIS DAN PENYEBAB MISKONSEPSI PADA MATERI GENETIKA BUKU SMA KELAS XII - Nusantari, Elya (Prodi Pendidikan Biologi FKIP UNS, 2011)
ABSTRACT- This research is aimed to reveal some misconception in genetic in some senior highschool handbook. Twelve biology books for highschool published during 2006-2010 have been reviewed. All those books show particular pattern of misconception that caused by misunderstanding about particular Mendelian approaches, inappropriate analogy and terminologies. Those misunderstanding lead to the misconception in the concept of chromose structure, protein syntheses, cell division, traits and mutation. Such misconceptions can be fix trhough the application of representative biomolecular approaches. Kata-kata Kunci: Misconception in genetics.